Exclusive breastfeeding and the risk of stunting, what does scientific evidence say? - Corputty, Lintje Sintje; Latuamury, Sitti R (CV. Paperhome Indonesia, 2025)
Background: Stunting is a global health problem that affects children's physical growth and cognitive development. Exclusive breastfeeding during the first six months of life is believed to reduce the risk of stunting. However, the direct link between exclusive breastfeeding and stunting prevention is still debated, with other factors such as the quality of complementary foods and socioeconomic conditions also affecting. Methods: This literature review used systematic searches through PubMed, ScienceDirect, Google Scholar, and Garuda databases, with relevant keywords regarding the relationship between exclusive breastfeeding and stunting. Selected articles must be relevant and published within the last five years, and include studies examining the impact of exclusive breastfeeding on stunting in children under five years of age. Results: Out of 440 articles found, ten relevant articles were selected for analysis. Some studies have shown a significant association between exclusive breastfeeding and a reduced risk of stunting in toddlers, but there are also studies that show that environmental and socioeconomic factors play an important role in stunting prevention. Conclusion: Exclusive breastfeeding has a key role in preventing stunting, but its success is influenced by various supporting factors such as social support, maternal knowledge, and environmental and socioeconomic conditions. Therefore, stunting prevention must be carried out with a more holistic approach that includes exclusive breastfeeding and improvement of external factors.